Understand The Novel Saturday With Fahter in The Perspective of Schleiermacher’s Hermeneutics - Julkarnain, Muhammad (Program Pascasarjana, UIN Alauddin Makassar, 2023)
The main problem in this paper is the effort or desire to understand a text well, according to Schleiermacher, is not an easy thing. The gaps in time, culture, language, and subjective experience between writers and readers or speakers and listeners make it difficult to capture the thoughts of the writer or speaker. For example, in the novel Saturday with Father written by Adhitya, culture, use of language, social structure, and educational background of the writer, which is different from the reader's, can trigger understanding. It takes a method that can overcome understanding, by Schleiermacher called hermeneutics. With this method the reader can extract the message, content and intent of the author by applying two approaches, namely grammatical and psychological interpretation. With grammatical interpretation, the reader will grasp the meaning of the text, and with psychological interpretation, the reader will experience subjectivity again and know things that the writer did not know. Thus, Schleiermacher's hermeneutics is called the hermeneutics of reproduction and production.